Weyl’s Theorem for Algebraically Ɱ* Quasi Paranormal Operators - V.Mallika; Dr. D. Senthilkumar (Utilitas Mathematica, 2025)
In this paper, a new operator Ɱ*quasi paranormal operator is introduced and studied. A bounded linear operator ???? in a Hilbert space ???? is said to be a Ɱ*